The Relationship between Facebook Use and Well‐Being depends on Communication Type and Tie Strength. Issue 4 (July 2016) - Burke, Moira; Kraut, Robert E.
Abstract : An extensive literature shows that social relationships influence psychological well‐being, but the underlying mechanisms remain unclear. We test predictions about online interactions and well‐being made by theories of belongingness, relationship maintenance, relational investment, social support, and social comparison. An opt‐in panel study of 1, 910 Facebook users linked self‐reported measures of well‐being to counts of respondents' Facebook activities from server logs. Specific uses of the site were associated with improvements in well‐being: Receiving targeted, composed communication from strong ties was associated with improvements in well‐being while viewing friends' wide‐audience broadcasts and receiving one‐click feedback were not. These results suggest that people derive benefits from online communication, as long it comes from people they care about and has been tailored for them.